A Case Study of RF Energy Harvesting for Wireless Sensor Network - Roy, Kousik; Ranjan, Prabhakar; Roy, Bhaskar; Billaha, A; Mondal, Bikash; sinha, Anu (International Journal of Computer Sciences and Engineering, 2025)
From conservation law of energy not possible to create or to destroy the energy but we can transform or change one form into another. The main purpose of this paper is to put light on the characteristics of radio frequency based energy harvesting systems. In all the cases mentioned above that the devices or the appliances can be operated without the usage of cables battery panels connectors which can make these devices more mobile and portable while operation and charging as well. These all can be achieved by RF energy harvesting system and the main reason for this is that it is accordingly free energy. The sources of RF based energy harvesting system are increasing day by day same as mobile based transmitters from which more and more energy can bring in. This paper more importantly focuses on parameters to design the system, methods, different frequency ranges that can be utilized and the respective circuitry for converting Low voltage output to High voltage for various applications using RF based energy harvesting.